DIFFERENCES IN RESULTS OF LEARNING EVALUATION OF DELIVERY CARE USING OSCE AND NON-OSCE - Een Nuraenah; Jujun Dwi Astuti; Syarifah (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2023)
The midwifery Diploma 3 education curriculum includes theoretical learning as wellas clinical skills that must be possessed to carry out proper midwifery practice.Learning evaluation should cover all areas including clinical skills. Delivery care isone of the main competencies that must be ensured by midwifery students. PoltekkesJakarta 3 Midwifery Department D3 Midwifery Study Program conducts evaluationsusing various methods. Clinical skills evaluation methods can be through OSCE ornon-OSCE.The purpose of this study was to find out the differences in the results of theevaluation of clinical skills in delivery care by comparing the OSCE and non-OSCEmethods.This research method uses descriptive analytic. The population in this study wereLevel II students of the D3 Midwifery study program, totaling 80 students. The resultsof this study indicate that the clinical skill passing rate of students using the OSCEmethod is 97.5% higher than that of the non-OSCE method, which is 95%. The groupof students who used the OSCE evaluation method with a mean of 3.40 and the classwith the non-OSCE evaluation method was 3.13. Based on the results of theIndependent T Test Samples statistical test, the results obtained a significance of0.001 (P value <0.005). These results indicate a significant difference between theevaluation results of the OSCE method and the non-OSCE method on the clinicalskills of midwifery students in Midwifery Care for Maternity. The results of this studyare in accordance with several other research results which recommend the OSCEmethod to be one of the evaluation methods in midwifery Diploma 3 education.